Photochemical reduction as a green method for the synthesis and size control of silver nanoparticles in κ-Carrageenan - Elsupikhe, R. F. (Institute of Electrical and Electronics Engineers Inc., 2016)
An eco-friendly photochemical method for preparing silver nanoparticles (Ag-NPs) in a natural polymer (κ-carrageenan) was successfully developed and is reported in this study. The Ag-NPs have been synthesized via a photochemical method by using UV-irradiation, silver nitrate and κ-carrageenan as a reducing agent, a silver precursor and a stabilizer at room temperature, at different irradiation time. The formation of Ag-NPs was improved by UV-vis spectroscopy where surface plasmon absorption maxima was observed at 420-430 nm. Transmission electron microscopy (TEM) data and the size distribution were in an agreement with the finding from the UV-vis spectra. Scanning electron microscope data illuminated the changes in the surface of κ-carrageenan. Fourier transform infrared spectra indicated the interactions between Ag-NPs and κ-carrageenan. In addition, the Ag-NPs were characterized by X-ray diffraction (XRD). The peaks in the XRD pattern showed that the Ag-NPs possessed an FCC structure. The green methods by using an eco-friendly stabilizer and reducing agent provide green and economic attributes to this paper. These results demonstrate the successful synthesis of Ag-NPs in κ-carrageenan by using UV-irradiation as a green and a photochemical reducing method. Ag-NPs were obtained by using UV-irradiation at different times at room temperature, where increasing irradiation time corresponded to the formation of smaller more spherical Ag-NPs. The synthesized Ag-NPs find applications as bacteria inhibitors and can be applied in the medical field.